Simian virus 40 origin- and T-antigen-dependent DNA replication with Drosophila factors in vitro. - Kamakaka, R.T.; Kaufman, P.D.; Stillman, B.; Mitsis, P.G.; Kadonaga, J.T. (Molecular and Cellular Biology, 1994)
DNA replication of double-stranded simian virus 40 (SV40) origin-containing plasmids, which has been previously thought to be a species-specific process that occurs only with factors derived from primate cells, is catalyzed with an extract derived from embryos of the fruit fly Drosophila melanogaster. This reaction is dependent upon both large T antigen, the SV40-encoded replication initiator protein and DNA helicase, and a functional T-antigen binding site at the origin of DNA replication. The efficiency of replication with extracts derived from Drosophila embryos is approximately 10% of that observed with extracts prepared from human 293 cells. This activity is not a unique property of embryonic extracts, as cytoplasmic extracts from Drosophila tissue culture cells also support T-antigen-mediated replication of SV40 DNA. By using highly purified proteins, DNA synthesis is initiated by Drosophila polymerase alpha-primase in a T-antigen-dependent manner in the presence of Drosophila replication protein A (RP-A; also known as single-stranded DNA-binding protein), but neither human RP-A nor Escherichia coli single-stranded DNA-binding protein could substitute for Drosophila RP-A. In reciprocal experiments, however, Drosophila RP-A was able to substitute for human RP-A in reactions carried out with human polymerase alpha-primase. These results collectively indicate that many of the specific functional interactions among T antigen, polymerase alpha-primase, and RP-A are conserved from primates to Drosophila species. Moreover, the observation that SV40 DNA replication can be performed with Drosophila factors provides a useful assay for the study of bidirectional DNA replication in Drosophila species in the context of a complete replication reaction.